MSME Growth in a Learning Perspective: an Examination of Work Experience, Self-Efficacy, and Financial Literacy - Diawati, Prety (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2025)
This study aims to analyse the influence of work experience, self-efficacy, access to financing, financial management skills, and financial literacy on MSME growth in Karawang Regency with entrepreneurial learning as a mediating variable. This research uses a quantitative approach with a survey method of 120 MSME actors selected through purposive sampling technique. The data were analysed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the help of SmartPLS 3 software. The results show that work experience and self-efficacy have a positive and significant direct effect on MSME growth, while access to financing, financial management skills, and financial literacy do not show a significant direct effect. However, all of the exogenous variables were shown to have significant indirect effects on business growth through entrepreneurial learning as a mediator. This finding reinforces the strategic role of Entrepreneurial Learning in bridging the influence of human and financial resources on business growth. This research provides a theoretical contribution to the development of Human Capital Theory and Entrepreneurial Learning Theory and suggests the need for MSME empowerment programme design that focuses on strengthening the entrepreneurial learning process in a practical, contextual, and sustainable manner.